E-Government Collaboration Research: A Theoretical Mapping - Verdico Arief; Irshad Ahmad Reshi; M. Amsyahar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
This research aims to reviews existing theories to be more complete and contain more contextual material, therefore it can be used as one of the references or guidance for the complex and dynamic e-government collaboration. This research tries to reviews a theory using theoretical mapping to various experts’ theories. In reviews theory, the researcher constructs a theoretical mapping based on some experts’ theories. Theoretical mapping is completed by looking deeper to the theory, then comparing the idea and concept of one theory to others, and creating the conclusion. If some experts share the same ideas, the researcher will compile the ideas into one indicator. In contrast, if an expert has an idea which is not delivered and recommended by others, then the idea will not be deleted or forcedly included to ones’ indicator, instead it will become a separate indicator. The result of the development theory which is done through theoretical mapping suggests some fundamental processes such as basic collaboration, planning, commitment and trust, leadership, communication relationship, and technological environment in carrying out e-government collaboration. The concept can be used as one of the references or guidance for developing, managing, forecasting or researching e-government collaboration, which currently has increasingly complex and dynamic problems.